Implementation of analog to digital converter for water leakage detection in pipeline using FPGA / Syafinas Mohd Salleh - Mohd Salleh, Syafinas (2012)
In this work, Analog to Digital Converter (ADC) circuit was designed to replace the Optical Spectrum Analyzer (OSA) to catch the data from the photo detector with FPGA as a control unit for water leakage detection. FPGA will receive the data and process the data to trigger an alarm for the water leakage system. DEI board by employing VHDL language was used to obtain the data from ADC in the form of voltage. Green LED was used to indicate that the voltage has been detected. The data then will be compared with the stored data, and if the leakage occurred on the pipe line Red LED, 7 segment and buzzer will activate.